Down-regulation of Human Leukocyte Antigen class I heavy chain in tumors is associated with a poor prognosis in advanced esophageal cancer patients - TANAKA, KIMITAKA (D.A. Spandidos, 2011)
The HLA class I antigen processing machinery (APM) plays a crucial role in the anticancer immune response. The aim of this study was to assess the clinical significance of APM components in esophageal cancer. A total of 11 esophageal cancer cell lines were evaluated by Western blot analysis for 13 HLA class I APM components. There was a different expression pattern among cancer cell lines for HLA class I heavy chain (HLA-HC), β2 microglobulin, Tapasin, TAP-1, TAP-2, LMP-7 and LMP-10. Immunohistochemical staining utilizing a tissue microarray method for HLA class I APM expression showing different expression patterns among cell lines was performed for 95 surgical specimens from patients with esophageal cancer. Prognostic factors were the down-regulation of HLA-HC, and the up-regulation of β2 microglobulin and TAP-1 in the cancer tissues. Multivariate analysis using a Cox regression model indicated that the down-regulation of HLA-HC, and up-regulation of TAP-1 in cancer tissues are independent, unfavorable prognostic factors (hazard ratio, 2.361 and 2.297; P=0.0141 and 0.0145, respectively). Although there was no significant difference in survival for selected p-stage I and II patients (n=54) in all APM components, only down-regulation of HLA-HC was an unfavorable prognostic factor by a Cox regression model for selected p-stage III and IV patients (n=41). In conclusion, the current results suggest that the down-regulation of HLA-HC in tumors is especially associated with a poor prognosis among advanced esophageal cancer patients.